THE COMMUNITY PARTICIPATION OF SCHOOL ADMINISTRATION BASED ON THE ARIYASACCA 4 THEPHARATPHITAYASAN SCHOOL UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE NAKHON SI THAMMARAT - Chairerk , Kittitiya; Srisuwan, Kasama; PhrakhruSumetpariyattikun (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aims to 1) study the state of school administration with community participation of Theparat Pittayasarn School, 2) study the school administration with community participation based on the principle of the Four Noble Truths of Theparat Pittayasarn School, and 3) present the school administration with community participation based on the principle of the Four Noble Truths of Theparat Pittayasarn School under the Office of the Secondary Education Service Area, Nakhon Si Thammarat. This research was conducted using qualitative research by conducting in-depth interviews with 15 relevant persons, interviews with 5 key informants, and focus group discussions with 7 experts. The research instruments were interview forms and focus group discussions. Data were analyzed using content analysis. The research results found that: The research results found that: 1) The conditions of educational institution administration with community participation of Theparat Phittayasarn School, under the Office of the Secondary Education Service Area, Nakhon Si Thammarat, consisted of (1) academic administration (2) personnel administration (3) budget management (4) general administration. The administration of educational institutions with community participation was based on the following principles: (1) Participation in expressing opinions (2) Participation in work (3) Participation in evaluation (4) Participation in support. 2) Guidelines for educational institution administration with community participation based on the principle of the Four Noble Truths. Theparat Phittayasarn School, under the Office of the Secondary Education Service Area, Nakhon Si Thammarat, consisted of 4 aspects: Area 1: Academic administration, with the following operational guidelines: (1) Curriculum and learning process development (2) Registration and evaluation (3) Management of learning subject groups and student development activities (4) Promotion of educational management quality (5) Development of educational technology innovation media and learning resources (6) Educational quality assurance; Area 2: Personnel administration There are the following operational guidelines: (1) Manpower planning and position determination (2) Recruitment, appointment and retirement from government service (3) Secretarial and divisional work (4) Discipline and maintenance of discipline (5) Efficiency enhancement work (6) Performance evaluation and salary increment work (7) Personnel record and promotion work. Part 3: Budget management has the following operational guidelines: (1) Budget planning and establishment work (2) Financial management (3) Accounting management (4) Material and asset management (5) Internal control and risk management. Part 4: General administration has the following operational guidelines: (1) Building and grounds work (2) Student affairs work (3) Health work (4) Public relations and community relations work. Educational institutions are administered with community participation based on the following principles: (1) Participation in expressing opinions (2) Participation in work (3) Participation in evaluation (4) Participation in support By using the principles of Buddhism as a framework for operations, namely the Four Noble Truths: (1) suffering, problem determination (2) origination, problem cause analysis (3) cessation, goal determination (4) the path, determining the method of problem solving, and 3) presenting the guidelines for school administration with community participation according to the principles of the Four Noble Truths of Theparat Phittayasarn School, it was found that it was appropriate, feasible, beneficial, and had a structure according to the components that could be applied.